Farm households' demand response to escalating food prices in Nigeria - Abigail Gbemisola Adeyonu; Adebayo Musediku Shittu; Mojisola Olanike Kehinde; Chioma Patricia Adekunle (Journal of Applied Economics, 2021)
This study examined food demand response to rising food prices among farm households in Nigeria using the three waves of the General Household Survey (Panel) conducted between 2010 and 2016. Analysis was within the Quadratic Almost Ideal Demand System framework from which price elasticities and compensated and uncompensated expenditure were computed. The results show that higher prices of almost all of the food categories affected their demand by households. Harvest and location dummies as well as household demographic variables were found to influence household food demand. Poor households consumed less of all the food categories compared to their non-poor counterparts. Escalating prices result in a welfare loss of household expenditure on commodity groups such as rice, wheat, pulses, tuber and other food and non-food items. Overall, 70.1% of the households suffered welfare loss that amounted to an average of 7.52% of the household budget annually.
Keywords: 330; Escalating prices; household food demand; Nigeria; QUAIDS